A history of Kenyan guitar music: 1945-1980 - Low, John (International Library of African Music, 1982)
Between November 1979 and April 1980, as part of a trip including several other African countries, I spent 5 months in Kenya. One of the musical projects that I planned to carry out during my stay was to study the guitar finger-styles that were common during the ’50s and ’60s. I did this by contacting Kenyan guitarists who used to play in this style, and by learning to play and sing their songs, as well as by making tape-recordings. In the course of this work I talked a lot with these artists and learned a great deal about their lives and the development of guitar music in Kenya. Although it had not been my original plan to do so, I eventually collected enough information to form the basis of an article on this subject. This information was provided by Joshua Ombima; William Umbima; William Osale; Johnson Ouko; David Jairo; George Agade; Jim Lasco Mugodo; Henry Viduyu; Tobias Oyugi; Daudi Kabaka; David Amunga; Ben Obolla; Fundi Konde; Peter Colmore; Silas Muiruri and Mtonga Wanganangu, without whose generous help this article could never have been written. I should add that, with the exception of the last four named, all my informants belong to either the Luhya or Luo people of Western Kenya. The article therefore has a definite bias towards Western Kenya, the home of so much fine Kenyan guitar music.
Keywords: Music; African Music; Kenya; Guitar Music